2010
DOI: 10.1051/0004-6361/201014393
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the gamma-ray emission of NGC 1275 and that of the Perseus cluster

Abstract: Context. The Gamma-ray emission from galaxy clusters hosting active galaxies is a complex combination of diffuse and point-like emission features with different spectral and spatial properties. Aims. We discuss in details the case of the Perseus cluster containing the radio-galaxy NGC 1275 that has been recently detected as a bright gamma-ray source by the Fermi-LAT experiment, in order to disentangle the sources of emission. Methods. We provide a detailed study of the gamma-ray emission coming from the core o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…The results of fifteen-year observation of NGC 1275 at energies from 800 GeV to 40 TeV are presented. A CM model [18] of gamma-ray emission of the Perseus cluster atmosphere and NGC 1275 is considered to describe the spectral properties of NGC 1275 in whole energy range. The Fermi LAT data at high energies and very high energy data from SHALON observations are well fitted in this model with three components [18], in which the most energetic and smaller blob produces a SSC emission observed at gamma-ray energies from MeV to TeV (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of fifteen-year observation of NGC 1275 at energies from 800 GeV to 40 TeV are presented. A CM model [18] of gamma-ray emission of the Perseus cluster atmosphere and NGC 1275 is considered to describe the spectral properties of NGC 1275 in whole energy range. The Fermi LAT data at high energies and very high energy data from SHALON observations are well fitted in this model with three components [18], in which the most energetic and smaller blob produces a SSC emission observed at gamma-ray energies from MeV to TeV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A CM model [18] of gamma-ray emission of the Perseus cluster atmosphere and NGC 1275 is considered to describe the spectral properties of NGC 1275 in whole energy range. The Fermi LAT data at high energies and very high energy data from SHALON observations are well fitted in this model with three components [18], in which the most energetic and smaller blob produces a SSC emission observed at gamma-ray energies from MeV to TeV (Fig. 9, red curve), whereas leptonic and hadronic models [18] of diffuse gamma-ray emission from the Perseus cluster (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this signal, also detected by Fermi-LAT (Abdo et al 2009), is consistent with an emission from the giant elliptical galaxy NGC 1275 lying at its centre (Aleksić et al 2010(Aleksić et al , 2012. From the Fermi-LAT results, Colafrancesco et al (2010) argue that it should be possible to resolve and detect the diffuse γ-ray flux of astrophysical origin coming from the outer corona of the Perseus cluster. Even more recently, Han et al (2012) reported a detection for Virgo, Fornax, and Coma from an analysis of Fermi-LAT data.…”
Section: Introductionmentioning
confidence: 99%